2015
DOI: 10.1111/joic.12192
|View full text |Cite
|
Sign up to set email alerts
|

Bypassing the Emergency Room to Reduce Door‐to‐Balloon Time and Improve Outcomes of ST Elevation Myocardial Infarction Patients: Analysis of Data from 2004–2010 ACSIS Registry

Abstract: Bypassing the ER is associated with significant shortening of DBT. This reduction, however, is not associated with any change in 30-day MACCE and 30-day or 1-year mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Based on the most recent ACSIS registry, thrombolytic therapy for acute STEMI is extremely rare in Israel. The standard of care in the vast majority of patients is PPCI [9]. In our series, none received thrombolytic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the most recent ACSIS registry, thrombolytic therapy for acute STEMI is extremely rare in Israel. The standard of care in the vast majority of patients is PPCI [9]. In our series, none received thrombolytic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that deprived neighborhoods present higher rates of mortality due to IHD [22][25]. Studies have investigated whether making reference cardiology services more accessible would ultimately reduce mortality rates [26][29]. Despite the extensive information about isolated factors, to our knowledge the interplay among distance from a reference cardiology center, socioeconomic/demographic conditions, and IHD-specific mortality rate have not been evaluated in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…After matching, the median VABT was 8 minutes (interquartile range [IQ] [6][7][8][9][10][11][12]) for the culprit PPCI first group, 12 minutes (IQ [9][10][11][12][13][14][15]) for the contralateral angiography first group, and 14 minutes (IQ [11][12][13][14][15][16][17]) for the complete angiography first group (P<0.001 overall and for trend). The median .001 for trend).…”
Section: What the Study Addsmentioning
confidence: 99%
“…9 Many strategies have been successfully applied to shorten door-to-balloon time before catheterization laboratory arrival but few have been studied to reduce delays inherent to the procedure. [10][11][12][13][14][15][16][17] Hereof, there is scarce data on the impact of obtaining a complete diagnostic angiography before PPCI. Our study sought to determine whether a strategy of performing culprit-vessel revascularization before obtaining contralateral or complete diagnostic angiography could be associated with a reduction in delays and outcomes in ST-segment-elevation myocardial infarction (STEMI) patients.…”
mentioning
confidence: 99%